Are older drivers' on-road driving error rates related to functional performance and/or self-reported driving experiences?. (June 2017) - Koppel, S.; Charlton, J.L.; Richter, N.; Di Stefano, M.; Macdonald, W.; Darzins, P.; Newstead, S.V.; D'Elia, A.; Mazer, B.; Gelinas, I.; Vrkljan, B.; Eliasz, K.; et al.
Highlights: Older drivers' on-road driving behavior was observed on two occasions approximately 12 months apart (Times 1 and 2) to determine whether the self-selected driving routes changed over time or whether their driving behavior changed over time. The on-road driving routes selected by older drivers at Time 2 were significantly shorter, contained significantly fewer driving maneuvers and had higher error rates than at Time 1. Older drivers' driving error rates were not related to functional performance and/or self-reported driving experiences among this presently healthy cohort of older drivers.